Refined numerical study on the effect of grouting plumpness on bearing behavior of pipe roof - Shi, Yufeng; Hu, Menghao; Zhang, Tao; Chen, Xiangsheng; Zhou, Yuhang; Min, Shichao; Jiang, Yalong (Frontiers in Materials, 2022)
Pre-supported pipe roof grouting is difficult to be full by various influences, which may have an impact on its bearing characteristics. In this paper, based on the preliminary experimental research, a refined numerical model considering the bonding between steel pipe and cement mortar was established to analyze the bending moment-deflection curve, the variation laws of ultimate bearing capacity coefficient and disengagement rate of pipe roof under different grouting plumpness, so as to obtain the influence of grouting plumpness on the bearing behavior of pipe roof. Meanwhile, the working conditions of reinforcement and casing in the pipe were conducted. The results show that compared with full grouting, the ultimate bearing capacity of the grouting pipe roof, pipe roof with reinforcement bundles and casing pipe decreases by 4.6%, 5.2% and 4.8% respectively when grouting incompleteness is 2%, and decreases by 35.3%, 40.4% and 37.1% respectively when grouting incompleteness rises to 25%; the ultimate bearing capacity of the pipe roof can be greatly improved by adding reinforcement bundles and casing pipe, and the increases of this case is 7.7%-18.3%, 31.4%-51.6% respectively; the disengagement rate of pipe roof and mortar under the same load increases with the increase of grouting incompleteness, which grows relatively slowly when the grouting incompleteness is less than 2%, and develops rapidly when it’s 2%-30%, while grows little when it’s more than 30%. Under the same grouting incompleteness, adding reinforcement bundles and casing pipe in the pipe roof can effectively reduce its debonding rate and the latter has better effect, and the corresponding disengagement rate is 62.8%-97.9% and 29.1%-91.9% of grouted pipe roof respectively.